통합간호역량 향상을 위한 간호교육의 전환: 증상 기반 임상추론에 대한 델파이 방법론 연구. - 김증임; 유소영; 박진희; 송주은; 류은정; 이주희; 임여진 (Journal of Korean Academy of Nursing, 2026)
Purpose: This study aimed to address the shift toward competency-based education and the planned 2028 "Integrated Nursing" National Licensing Examination (NLE), this study aimed to establish structural alignment among NLE domains, the seven integrated nursing competencies (INCs), and curriculum goals, with a particular focus on implementing symptom-based clinical reasoning (SBCR). Methods: This Delphi-based methodological study included seven content experts for content validity index (CVI) assessment and 24 nursing education experts who participated in a consensus workshop. The item-level CVI and the scale-level CVI/average were calculated to confirm the linkage between INCs and NLE domains. In addition, qualitative analysis of workshop materials and meeting records was conducted to derive 10 integrated learning topics and to develop an SBCR educational model for the key symptom of headache, grounded in Miller's Clinical Competence Pyramid (levels 2-4). Results: The analysis confirmed the validity of integrating the INCs within the overall curriculum structure. The resulting framework delineates staged learning objectives and core clinical questions designed to systematically enhance clinical reasoning, promote safe nursing practice, and support professional reflection within a unified curriculum. Conclusion: This study provides a practical foundation for nursing curriculum redesign by facilitating a transition from fragmented, subject-based instruction to a holistic, patient-centered SBCR model. This approach aligns with the requirements of the integrated NLE and is expected to contribute to meaningful improvements in actual clinical competency.